กระบวนการก่อสร้างที่อยู่อาศัยโดยระบบชิ้นส่วนสำเร็จรูป : กรณีศึกษา โครงการชลลดา รัตนาธิเบศร์ - บุษบง เจริญพันธ์โยธิน (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
The main purposes of this study were to research the process of partial precast techniques and the use of partial precast in housing construction. In addition, it studied the partial precast in terms of quality, duration and cost based on the construction of two-storey detached houses with functional areas of 95 square meters. The study was carried out through observing, recording and taking photographs of the manufacturing process and installation process. According to the case study, 950 houses were built by using precast reinforced concrete. They were detached houses with functional areas between 95 square meters and 150 square meters. Ground pole post, beams, bathroom floor and porch floor were ready-made products manufactured in a factory on site. Such products were equipped with iron sheets implanted in the concrete where bonding areas were. The products were joined together by soldering the iron sheets to strengthen the house. The factory covered an area of 2 rai. Its construction cost was 2,285,259 baht. The products were transported to the construction site by a crane weighing 21 tons. During a 1-day observation, by using precast products 4 houses could be finished. To finish 10 two-storey detached houses with a 95-square-meter functional area by using precast products, 22 people were involved. They were 1 project manager, 3 supervisors, 7 carpenters, 3 blacksmiths, 7 installation workers and 1 expert in iron soldering. This expert had to have a certificate. The construction lasted 22 days. The total cost of manufacturing and installing the products was 153,063 baht per house or 1,611 baht a square meter. The duration of the study was from June, 2002 to January, 2003